The quality of digital screening & diagnostic mammographic images using standard PGMI criteria in Hospital Universiti Sains Malaysia - Syed Abas, Sharipah Intan Shafina (2015)
Introduction: The mammography has its own unique quality assurance program in order to produce a constantly high quality images. It emphasizes on quality control (QC) such as direct equipment assessment (mammogram machines) and quality audits i.e. film reject analysis and PGMI which acts as an indirect assessment tool for personnel involved; mainly radiographers PGMI is a part of standard quality audit for mammogram and widely practiced in many countries. Objectives: In HUSM, the audit of mammogram using PGMI was never performed for rating image quality. PGMI rating comprised of criteria determining mammograms as perfect, good, moderate and inadequate. The College of Radiology Malaysia guidelines recommends >97% of images to be in perfect, good or moderate categories with overall 75% in the perfect & good groups; >3% in the perfect group; and <3% of images to be classified inadequate. Methodology: Digital mammograms from 107 consecutively screened and diagnostic mammograms were sourced in two centers; namely HUSM and HRPZII. Test sets were enriched with mammograms from each PGMI category and independently scored by six radiographers, each with ≥3 years' experience, using PGMI. Each image was individually scored P, G, M, or I. Reasons for scoring less than perfect were documented and each mammogram assigned an overall PGMI score. Test sets were compared with an expert observer. Results: PGMI standard: The overall rating in HUSM for perfect, good and moderate (PGM) rating were calculated as 98%. This was acceptable to the standard set by Malaysian College of Radiology (>97%). While in the perfect & good groups (PG); it was lower than standard which was 52% (QA standard is 75%). As for perfect, its proportion was 15% (QA standard is >3%) and for inadequate was 2% (QAP standard is < 3%). PGMI inter-observer reliability among radiographers’ shows overall poor agreement with κ = 0.18. Most images with poor agreement were related to good and moderate image rating whereas PGMI inter-observer reliability radiographers’ vs. Radiologist shows overall poor agreement with κ = 0.20 and most images with poor agreement were related to good, moderate and inadequate images. Conclusion: Reliability of PGMI must be improved as current study showed its variability and subjective interpretation. Efforts must be made for improvements or modifications of PGMI in order to reduce its subjectivity and maintains its efficiency.